Optimization of Temperature Exhaust and Peltier Elements to Thermoelectric Generator Output - Irwan Setyowidodo,Am. Muffarih,Sutanto,Irma Mar’atus Sholihah,Aprilia Dwi Handayani (International Conference on Industrial Revolution for Polytechnic Education, 2020)
The number of small and medium sized metal smelting industries whose working processes produce large waste heat energy. This results in almost 40% of energy being wasted as high temperature exhaust gases. This percentage is able to be converted into electrical energy with the concept of a thermoelectric generator using peltier elements. The way to use it is to use TEG (Thermoelectric Generator) whose function is to convert heat into electricity by utilizing temperature differences. The purpose of this research is how exhaust temperature optimization, the number of peltier elements to the thermoelectric generator voltage output on a used metal melting furnace. Then the analysis is done to get the optimum Seebeck coefficient as a representation of the thermoelectric generator performance. The design of this study is an L20 orthogonal matrix with three replications using a factorial design. The independent variables varied were exhaust temperature, number of peltier elements and data analysis using ANOVA Two Way. Based on the results of the research data it can be concluded that the furnace wall temperature affects the TEG current output. Where the most optimal wall temperature is 480 ºC which produces a TEG current output of 168 mA. This indicates an increase in the temperature of the used metal smelting furnace walls increasing the TEG current output. While the number of peltier elements does not influence the TEG current output